Answer :


Rearranging the terms we get:




Integrating both the sides we get:



y = x2 + log|x| + c


y = 1 when x = 1


1 = 12 + log1 + c


1 - 1 = 0 + c (log1 = 0)


c = 0


y = x2 + log|x|


Ans: y = x2 + log|x|


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve the followiRD Sharma - Volume 2

tan-1xMathematics - Exemplar

The number of solMathematics - Exemplar

Find the particulMathematics - Board Papers

Solve the followiRD Sharma - Volume 2

Find the particulMathematics - Board Papers